1998
DOI: 10.1136/bjo.82.10.1131
|View full text |Cite
|
Sign up to set email alerts
|

Ocular contact time of a carbomer gel (GelTears) in humans

Abstract: Background/aims-Carbomers are widely used in products for the treatment of dry eye; however, the polymer gel thins on addition of probes (for example, fluorescein salt) confounding the comparison of products by objective clinical tests such as spectrophotofluorimetry or scintigraphy. A novel method of radiolabelling carbomer gels, with minimum change to their rheology, has permitted the noninvasive evaluation of precorneal residence of the gel in volunteers using gamma scintigraphy. Tc-DTPA labelled saline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 3 publications
0
37
0
1
Order By: Relevance
“…2) However, the rapid turnover of lacrimal fluid and extensive nasolacrimal drainage 3) along with eyes blinking reflex rapidly eliminate the administrated eye drops. 4,5) This causes short pre-corneal residence time, which limits effective transcorneal drug absorption.…”
mentioning
confidence: 99%
“…2) However, the rapid turnover of lacrimal fluid and extensive nasolacrimal drainage 3) along with eyes blinking reflex rapidly eliminate the administrated eye drops. 4,5) This causes short pre-corneal residence time, which limits effective transcorneal drug absorption.…”
mentioning
confidence: 99%
“…16 C-57BL/6 mice were equally divided into five groups i) control; ii) ERL; iii) ERL plus control vehicle; iv) ERL plus PES_103 0.1%; v) ERL plus commercially available artificial tears (Carbopol974 -Trade Name SiccaFluid ® ) [31,32]. The eyes of each group were selected so as to avoid both eyes of a mouse being assigned to the same treatment group, with the only exception of the control group.…”
mentioning
confidence: 99%
“…Carbomer is a water-soluble polymeric resin with a relative molecular weight of 4×10 6 . It was reported that polyacrylic acid gel maintained the tear film in contact with the eye for an extended period [12,13] . As shown in this study, the precorneal residence time of carbomer gel was significantly longer than that of 1% CMC.…”
Section: Discussionmentioning
confidence: 99%
“…Carbomer (polyacrylic acid) is a water-soluble polymeric resin that has been reported to maintain the tear film in contact with the eye for an extended period [12,13] . In our previous work, we prepared a carbomer based gel.…”
mentioning
confidence: 99%